Land tenure security for water settlement area: a preliminary study / Farah Zaini ... [et al.] - Zaini, Farah; Abd Aziz, Shyafiena; Yusuf, Adibah; Ali, Nurlaila (2021)
Land tenure is a complicated concept that comes in a variety of forms. Concerns about tenure and property rights have been linked to population displacement, food insecurity, and environmental degradation. The security of land tenure property rights in water villages should be safeguarded, as small-scale fishing communities contribute significantly to food security, inclusive economic growth, and other critical development goals. This article is the result of a preliminary study on securing land tenure for the Water Village community. The current practices of water village land tenure were ascertained through qualitative interviews with the village heads of three water villages in Northern Sarawak. Thematic analysis was used to deduce land ownership practices such as type of land ownership, documentation of land ownership, and property transaction. It can be concluded that while current practices are convenient, they could be improved to better protect the water village area's land tenure and property rights.